2007
DOI: 10.1194/jlr.m600414-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The association of C-reactive protein with an oxidative metabolite of LDL and its implication in atherosclerosis

Abstract: C-reactive protein (CRP) is one of the strongest independent predictors of cardiovascular disease. We have previously reported that oxidized LDL (oxLDL) interacts with b2-glycoprotein I (b2GPI), implicating oxLDL/b2GPI complexes as putative autoantigens in autoimmune-mediated atherosclerotic vascular disease. In this study, we investigated the interaction of CRP with oxLDL/b2GPI complexes and its association with atherosclerosis in patients with diabetes mellitus (DM). CRP/oxLDL/b2GPI complexes were predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…It has been shown that nonalcoholic fatty liver disease, including hepatic steatosis, is closely related via enhanced inflammation to insulin resistance, metabolic syndrome, and cardiovascular disease [21][22][23][24] . Tabuchi et al 25) reported that ezetimibe inhibits the absorption of oxidized cholesterol and its deposition in the liver. Using a rat model of metabolic syndrome, Deushi et al 26) documented that ezetimibe improved liver steatosis and insulin resistance by decreasing hepatic lipid deposition and fibrosis of the liver and effectively reduced systemic dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that nonalcoholic fatty liver disease, including hepatic steatosis, is closely related via enhanced inflammation to insulin resistance, metabolic syndrome, and cardiovascular disease [21][22][23][24] . Tabuchi et al 25) reported that ezetimibe inhibits the absorption of oxidized cholesterol and its deposition in the liver. Using a rat model of metabolic syndrome, Deushi et al 26) documented that ezetimibe improved liver steatosis and insulin resistance by decreasing hepatic lipid deposition and fibrosis of the liver and effectively reduced systemic dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…. The generation of CRP=OxLDL= b2GPI complexes seems to be associated with arterial inflammation, hyperglycemia, and hypercholesterolemia (277). Immunohistochemistry staining co-localized OxLDL, b2GPI, and CRP in carotid artery plaques (277).…”
Section: A Systemic Lupus Erythematosus and Antiphospholipid Syndromementioning
confidence: 99%
“…A couple such as C-reactive protein (CRP), soluble forms of lectin-type OxLDL receptor-1, or small dense LDL are of interest, because CRP and sLOX-1 could bind to OxLDL and small dense LDL is thought to be susceptible to oxidative modification [56][57][58] . It is certainly necessary to correlae plasma OxLDL levels and these other markers and their clinical relevance in the future.…”
Section: Some Controversial Studiesmentioning
confidence: 99%